WASHINGTON DELGADO: EXPLICIT EXERCISES OF AN AERIAL POETICS - coello, Oscar (2007)
Taking the perspective of classic semiotics, this article analyzes the explicit poetics inDelgado· s Parque, and looks for the related links between literary postula tes and themeanings in the book, a task made possible through an examination of the semanticlevels of discourse.